Optimizing Stimulation of Students with Disabilities - Rahma Ardiani; Pramesti Pradna Paramita (Psikostudia : Jurnal Psikologi, 2024)
Problems often experienced by people with disabilities are the inability to respond quickly, difficulty controlling emotions, concentrating attention problems, difficulty applying language fluently for daily communication. The goal of this research is to describe stimulation for people with disabilities to fulfil their daily needs. The method used narrative review by taking from google scholars and JSTOR, so that found 13 journals are obtained from 2014-2024.Based on the reviews are people with disabilities have different limitations according to the types. The stimulation can provide independence, overcome the stigma, make things easier in academic and work contexts. Stimulations that ca be applied is communication and language practice, so they can interact with non-disabled people, then the stigma can be minimized. Activities of daily living should be available for all types, so they can regulate themselves independently. Motoric stimulation to support children’s mobilization as well as stimulation to increase attention and concentration. It can be concluded that stimulation can help people with disabilities achieve their potential, overcome obstacles, and manage themselves.Masalah yang sering dialami penyandang disabilitas yaitu ketidakmampuan merespon secara cepat, kesulitan mengontrol emosi, masalah pemusatan perhatian, kesulitan menerapkan bahasa yang baik sebagai komunikasi sehari-hari. Tujuan penelitian ini adalah untuk mendeskripsikan stimulasi bagi penyandang disabilitas dalam rangka pemenuhan kebutuhan hidup sehari-hari. Metode penelitia yang digunakan yaitu narrative review dengan mengambil data dari google scholar dan JSTOR, sehingga diperoleh 13 jurnal mulai tahun 2014 hingga 2024. Berdasarkan hasil review penyandang disabilitas memiliki keterbatasan yang berbeda sesuai jenis kebutuhan. stimulasi yang diberikan dengan tujuan mampu meningkatkan kemandirian, mengatasi stigma, memudahkan dalam konteks akademis dan pekerjaan. Stimulasi yang dapat diterapkan penyandang disabilitas, misalnya stimulasi komunikasi dan bahasa. Dimana dalam hidup bersosial tidak lepas dari berinteraksi baik sesama disabilitas maupun non disabilitas, sehingga dapat meminimalisasi stigma yang ada. Stimulasi activities of daily learning (ADL) menjadi stimulasi yang seharusnya ada di seluruh jenis disabilitas, supaya dapat mengatur dirinya secara mandiri. Stimulasi motorik sebagai penunjang mobilisasi anak, serta stimulasi peningkatan atensi sehingga siswa dapat konsentrasi menyelesaikan tugas-tugasnya dengan optimal. Dengan demikian stimulasi dapat membantu penyandang disabilitas mencapai potensi, menangani hambatan, dan mengelola diri secara mandiri.